Pengaruh Sikap Siswa pada Mata Pelajaran Bahasa Indonesia terhadap Keterampilan Menulis Karangan Argumentasi Siswa Kelas X di SMA PGRI 4 Jakarta - Prameswari, Jatut Yoga (Lembaga Penelitian STKIP PGRI Bandar Lampung, 2017)
This study aims to describe the influence of studentsâ attitudes on Indonesian subjects towards studentsâ ability in writing argumentative essay. The method used to carry out this research is to associative method. This method examines the effect of the two variables. In this method, the attitude of students in Indonesian subject is as free variables and the ability to write the argumentative essay is as the dependent variable. After doing research on the influence of studentsâ attitudes on Indonesian subjects towards studentsâ ability in writing argumentative essay at class X of SMA PGRI 4 Jakarta through associative method, finally the author can draw the conclusion that is the attitude of the students on the subjects of Indonesian had significant influence studentsâ ability in writing argumentative essay at class X of SMA PGRI 4 Jakarta, as evidenced by the acquisition value of the correlation (r) of 0.322.